Studies of noctilucent clouds from the stratosphere during the SONC balloon-borne experiment in 2021. (15th November 2022) - Dalin, P.; Suzuki, H.; Pertsev, N.; Perminov, V.; Efremov, D.; Voelger, P.; Narayanan, V.L.; Mann, I.; Häggström, I.; Zalcik, M.; Ugolnikov, O.; Hedin, J.; et al.
Abstract: On the night 16–17 August 2021, a balloon-borne experiment called Stratospheric Observations of Noctilucent Clouds (SONC) was successfully performed. A big scientific balloon, having onboard three automated cameras for studies of noctilucent clouds (NLC), was launched to 32.7 km altitude from Esrange (northern Sweden). All three NLC cameras and electronics were completely operational in the stratosphere for more than 10 h at low temperatures of about −30 °C. Two wide angle cameras registered an extended NLC field of about 1700 km long in the twilight sky sector from the north-west to the north-east of Esrange. NLC were of a moderate brightness and were located at high latitudes between 68° and 71°N. The NLC field was located in a cold area (138–142 K) below the frost point temperature (145–148 K) in the mesopause region that was confirmed by Aura/MLS satellite and Esrange lidar measurements. The balloon-borne NLC measurements were accompanied by ground-based lidar and radar measurements. The latter have registered Polar Mesosphere Summer Echoes (PMSE) in the same volume of the summer mesopause along with NLC observed from the stratosphere that has been performed for the first time above northern Scandinavia. We describe the technique and method of the NLC observation from the stratosphere as well as present the first scientific results of the SONC experiment. Highlights: Balloon experiment was successfully realized to study NLC from the stratosphere. NLC field had horizontal scales of about 1700 km long from east to west. NLC and PMSE were simultaneously observed in a common mesopause volume. NLC field was located in a cold area of the mesopause.